Diagnosis, treatment and immunopathogenesis of the HIV-associated tuberculosis immune reconstitution inflammatory syndrome - Meintjes, Graeme (Department of Medicine, 2015)
The paradoxical tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) is a frequent complication of antiretroviral therapy (ART) among patients who start ART while on treatment for tuberculosis (TB). The condition manifests with new, worsening or recurrent inflammatory features of TB due to immunopathology attendant on rapidly recovering immune function.